Poetics of Slow Cinema Nostalgia, Absurdism, Boredom - Çağlayan, Emre (Springer International Publishing, 2018)
This book discusses slow cinema, a contemporary global production trend that has recently gained momentum in film theory and criticism. Slow films dispense with narrative progression in favour of a contemplative mood, which is stretched out to the extreme in order to impel viewers to confront cinematic temporality in all its undivided glory. Despite its critical reputation as an oblique mode of film practice, slow cinema continues to attract, challenge and provoke audiences. Focusing on filmmakers Béla Tarr, Tsai Ming-liang and Nuri Bilge Ceylan, this book identifies nostalgia, absurd humour and boredom as intrinsic dimensions of slow cinema and explores the ways in which these directors negotiate local filmmaking conventions with the demands of a global cinephile niche. As the first study to treat slow cinema both as an aesthetic style and as an institutional discourse, Poetics of Slow Cinema offers an illuminating perspective on the tradition's historical genealogy and envisions it with a Janus-faced disposition in the age of digital technologies-lamenting at once the passing of difficult, ambiguous modernist film and capitalizing on the yearning for its absence.